Hydrochemistry of Lake Licheńskie between December 2014 and November 2015 - Woszczyk, Michał (PANGAEA, 2024)
The L1 is the deepest site of the lake (12.6 m). Hydrochemical measurements were performed with monthly resolution between December 2014 and November 2015. Lake water parameters (t, pH, EC, dissolve O2) so as trace gases (CH₄ and N₂O) were measured every 1 m from the surface to the near bottom layer. t, pH, EC and O2 were determined in situ with a YSI Professional Plus probe, calibrated and checked with certified reference material (Harbour water, NWHAMIL-20.2) beforehand. Trace gases were analysed in the laboratory. The surface water samples for trace gas analyses were collected directly at the air-water interface by hand and the deeper water layers were sampled using a Ruttner sampler (KC Denmark A/S). The water for trace gases was preserved with KOH powder (min. 85 wt. %; c.a. 1 g) and kept in amber glass 100 mL serum bottles stoppered with butyl septa and crimped with Al seals. Until the measurements the samples were stored in the dark in a cool box (at 4°C). For CH₄ and N₂O analysis a 20% N2-filled headspace volume was created. Then, after initial hand shaking, the samples were left overnight to equilibrate at a constant room temperature and analysed with a gas chromatograph (GC; Agilent). For the analysis of CH₄ a Carboxen 1010 Plot 30m x 0.53mm x 30µm column (Supelco) and a flame ionization detector (FID) was used. For N2O a GS-Carbonplot 30m x 0.32mm x 3µm (Agilent Technologies) column and an electron capture detector (ECD) was used. Concentrations of CH₄ and N₂O were obtained via peak integration and using the functions for gas pressure, headspace volume, ambient temperature, salinity and Bunsen solubility coefficients summarized by Wiesenburg and Guinasso (1979) as well as Weiss and Price (1980). For quality control gas standards (CH₄ in N₂ 100.0 ± 1.5 ppm mol and N₂O in N₂ 100.0 ± 1.5 ppm mol; PanGas; Switzerland) were used. Limit of quantification of our GC measurement was 1 ppm for CH₄ and 0.2 ppm for N₂O. Analtical error was estimated to ± 5%.
Keywords: Anthropogenic impact; fluxes; Lake; Methane; nitrous oxide